Monitoring α-synuclein aggregation - Juan Estaun-Panzano; Marie-Laure Arotcarena; Erwan Bezard (Neurobiology of Disease, 2023)
Synucleinopathies, including Parkinson's disease (PD), dementia with Lewy Bodies (DLB), and multiple system atrophy (MSA), are characterized by the misfolding and subsequent aggregation of alpha-synuclein (α-syn) that accumulates in cytoplasmic inclusions bodies in the cells of affected brain regions. Since the seminal report of likely-aggregated α-syn presence within the Lewy bodies by Spillantini et al. in 1997, the keyword “synuclein aggregation” has appeared in over 6000 papers (Source: PubMed October 2022). Studying, observing, describing, and quantifying α-syn aggregation is therefore of paramount importance, whether it happens in tubo, in vitro, in post-mortem samples, or in vivo. The past few years have witnessed tremendous progress in understanding aggregation mechanisms and identifying various polymorphs. In this context of growing complexity, it is of utmost importance to understand what tools we possess, what exact information they provide, and in what context they may be applied. Nonetheless, it is also crucial to rationalize the relevance of the information and the limitations of these methods for gauging the final result. In this review, we present the main techniques that have shaped the current views about α-syn structure and dynamics, with particular emphasis on the recent breakthroughs that may change our understanding of synucleinopathies.